ANTIOXIDANT ACTIVITY AND DETERMINATION OF TOTAL TANNIN CONTENT OF 70% ETHANOL EXTRACT OF PLETKAN LEAVES (Ruellia tuberosa L. - Wirman, Adia Putra (Fakultas Kedokteran, 2025)
Pletekan leaves are found in many regions in Indonesia, traditionally used for the treatment of hypertension, diabetes and antioxidants. Pletekan plants contain tannin compounds with phenol groups which are known to have biological effects such as antioxidants through mechanisms as free radical traps and electron donors. The aim of the research was to determine antioxidant activity using the ABTS (2,2-azinobis 3- ethyl benzothiazoline-6-sulfonic acid) method and testing total tannin content using the spectrophotometric method and Folin-Ciocalteu reagent and tannic acid as standards. Based on the research results, the 70% ethanol extract of Pletekan leaves has antioxidant activity as a free radical reducer which is in the medium category with an IC50 value of 215.07 ± 11.65µg/ml while the total tannin content is 114.60 ± 4.1 mg TAE/g.